(untitled) (International Journal of Automation and Smart Technology, 2015)
In contrast to conventional manufacturing, digital manufacturing is not affected by marginal costs; that is, the cost for producing a single prototype is not different from producing several thousand ones. Digital manufacturing consequently eliminates the requirement for large sums of capital necessary for conventional manufacturing. Digital manufacturing combined with cloud platforms and cloud-enabled databases will allow large-quantity virtual product development while minimizing costs, which will consequently reflect on the efficient manufacturing of physical products.